Sistem Pendukung Keputusan Menentukan Lokasi Pembangunan Jaringan Internet Menggunakan Metode Profile Matching - Agustina, Safira; Rohayani, Hetty; Marthiawati H, Noneng; Azzamy, Muhammad Nabil (Journal of Computer System and Informatics (JoSYC), 2024)
Decision Support Systems are interactive information systems that provide information, modeling, and data manipulation. This system is used to assist decision-making in semi-structured s and unstructured situations, where no one knows for sure how the decision should be made. The problem in this study is, determining the location of Internet network installation by BeeBeeNet, carried out based on the company's decision to determine a new location to build an Internet network in a new area, namely by surveying the area, as well as looking at the population density in an area and the current interest of the community. The purpose of making a Decision Support System for determining the location of building an internet network is to determine the right location. The method used in this research is the Profile Matching method, which is a Decision Support system in the location criteria determined by PT Batanghari Vision so that the difference in competence (GAP) can be known. The results obtained are the results of ranking using the profile matching method, using several candidates to get results in determining the new location for building an internet network, from the calculations carried out the highest value is 2.9555, this value is the highest value of the existing location criteria. the results obtained can be the right result for the company to choose the location of the internet network construction in the new location.